2012
DOI: 10.2217/imt.12.110
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Leishmania Tarentolae Encoding the HPV Type 16 E7 gene in Tumor Mice Model

Abstract: Overall, the results obtained revealed that the E7-GFP recombinant L. tarentolae could be a potential live vaccine for induction of immune responses in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 62 publications
1
21
1
Order By: Relevance
“…A recombinant L. tarentolae expressing HIV-1 Gag protein induced strong cell-mediated immunity in mice and decreased HIV-1 replication in an ex vivo system, suggesting that this species can be applied as a promising live vaccine against intracellular pathogens [10]. Recently, a recombinant L. tarentolae strain expressing HPV-E7 antigen-green fluorescent protein (GFP) was developed and showed a potential as a live vaccine against HPV infection [36]. Additionally, modification of, and insertion into, the genome of L. tarentolae can be done easily and there is no insert size limitation making it a versatile tool for vaccine development.…”
Section: Discussionmentioning
confidence: 99%
“…A recombinant L. tarentolae expressing HIV-1 Gag protein induced strong cell-mediated immunity in mice and decreased HIV-1 replication in an ex vivo system, suggesting that this species can be applied as a promising live vaccine against intracellular pathogens [10]. Recently, a recombinant L. tarentolae strain expressing HPV-E7 antigen-green fluorescent protein (GFP) was developed and showed a potential as a live vaccine against HPV infection [36]. Additionally, modification of, and insertion into, the genome of L. tarentolae can be done easily and there is no insert size limitation making it a versatile tool for vaccine development.…”
Section: Discussionmentioning
confidence: 99%
“…Its higher sensitivity to CIN screening may become a major tool to screen cervical cancer in women over 30 years old. HPV virus can not be cultivated in vitro, and the immunoreactions easy to detect can also not be induced in vivo (Salehi et al, 2012), so its diagnosis and classification are not be detected with serological test. In recent years, a lot of literatures revealed that persistent HPV infection is a high-risk factor of cervical cancer, especially highrisk HPV infection which is one of the causes that result in the high-grade lesion of cervical cancer and CIN.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, we showed that a recombinant L. tarentolae strain expressing high levels of full-length HPV16 E7 was immunogenic and could induce the production of IFN-g cytokine. Furthermore, the protective effects of both subcutaneously DNA and live vaccine strategies were similar in tumor mice model (Salehi et al, 2012). These data indicated that further studies are required to increase live vaccine efficacy using different potent components such as adjuvants.…”
Section: Introductionmentioning
confidence: 72%